Male reproductive toxicity of inorganic nanoparticles in rodent models: A systematic review. (25th August 2022) - Dantas, Graziela P.F.; Ferraz, Fausto S.; Andrade, Lídia M.; Costa, Guilherme M.J.
Abstract: The use of nanoscale materials for different biomedical applications has grown a lot in the last years and raised several concerns about toxic effects on human health. Several studies have shown that different types of NPs may exert toxic effects on organs such as the brain, the liver and the kidney. However, The toxicological effects of inorganic NPs on reproductive organs only recently has attracted attention. This systematic review selected data published in the last twelve years assessing rodent-male in vitro and in vivo reproductive toxicity caused by different types of inorganic nanoparticles (AgNPs, AuNPs, IONPs, ZnONPs, TiO2NPs and NiNPs). Structural and functional alterations were commonly observed in Sertoli, Leydig, germ and sperm cells in vitro and in vivo . Oxidative stress, apoptosis, and/or necrosis were the most common findings after inorganic nanoparticle exposure. The toxicity of different NPs depends strongly on their physicochemical characteristics and intrinsic properties. Although a broad overview of the toxicity of different inorganic NPs was found in the papers evaluated, the results are highly variable due to the lack of standardization of protocols, regarding NPs sizes, concentration/doses, and routes of administration. Despite focusing on the effect of different nanoparticles on male reproduction, the mechanisms and pathways related to cellular and/or organ toxicity were poorly discussed. Understanding the specific molecular interactions between NPs and male testicular cells is crucial for developing nanobiotechnologies related to reproductive medicine. Graphical abstract: In vitro and in vivo male reproductive cell toxicities caused by inorganic nanoparticles. Inorganic NPs can penetrate the cell membrane and nucleus, causing several adverse effects, such as oxidative stress, lipid peroxidation, apoptosis, DNA and mitochondrial damage, and sperm defects. These mentioned effects can reduce animal fertility. I.P. = intraperitoneal; I.V. = intravenous. Image 1 Highlights: Inorganics NPs are being tested for reproductive applications. Inorganics NPs cause in vivo and in vitro toxic effects in testicular cells. Despite the route of administration, inorganic NPs can affect spermatogenesis. Gold and iron nanoparticles tend to be more biocompatible. Several types of inorganics NPs induce oxidative stress.